2009
DOI: 10.1111/j.1468-1331.2009.02708.x
|View full text |Cite
|
Sign up to set email alerts
|

One‐year MRI scan predicts clinical response to interferon beta in multiple sclerosis

Abstract: Developing new T2-hyperintense lesions during IFNB treatment was the best predictor of long-term poor response to therapy. MRI scans performed after 1 year of IFNB treatment may be useful in contributing to early identification of poor responders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
2
8

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(110 citation statements)
references
References 32 publications
(36 reference statements)
7
93
2
8
Order By: Relevance
“…18,59,[90][91][92][93][94][95][96][97][98][99][100] For example, RRMS and CIS patients with elevated Gd+ and T2 lesion activity, in terms of number or volume of lesions before or after therapy, have a greater likelihood of subsequent clinical relapses, disability progression, cognitive impairment, decreased quality of life, and even death as compared with patients with lower or absent MRI activity. 18,59,[90][91][92][93][94][95][96][97][98][99][100] Although most of these studies have been relatively short term, some have followed study cohorts for 20 or more years. [100][101][102] …”
Section: Discussionmentioning
confidence: 99%
“…18,59,[90][91][92][93][94][95][96][97][98][99][100] For example, RRMS and CIS patients with elevated Gd+ and T2 lesion activity, in terms of number or volume of lesions before or after therapy, have a greater likelihood of subsequent clinical relapses, disability progression, cognitive impairment, decreased quality of life, and even death as compared with patients with lower or absent MRI activity. 18,59,[90][91][92][93][94][95][96][97][98][99][100] Although most of these studies have been relatively short term, some have followed study cohorts for 20 or more years. [100][101][102] …”
Section: Discussionmentioning
confidence: 99%
“…While the value of MRI measurements in treatment trials is acceptable, the utilization in everyday clinical practice has only been established in recent years. Several studies have demonstrated that the occurrence of new T2 lesions or Gd-enhancing T1 lesions during the first year of a treatment (most studies have investigated treatment with interferon-β) correlates with progression of disability [31,32]. Thus, the Fig.…”
Section: Mr Imaging In Monitoring and Predicting Treatment Responsementioning
confidence: 99%
“…46,47 While it is generally understood that relapses in MS result in cumulative disability, the direct relationship between successive relapses and disability progression has been difficult to demonstrate in clinical trials. 49 An observational study that examined the effect of relapses (defined as the appearance of a new neurological symptom [or a worsening in a previous symptom], lasting more than 48 hours, without fever) on disability progression found that having 1 or more relapses during the first 2 years of IFNβ treatment was associated with earlier progression of disability.…”
Section: 42mentioning
confidence: 99%
“…36 Relapses are also important to quantify because they can be associated with significant residual deficits, and relapse rate in the early stages of the disease can be a key determinant of later accumulation of disability. 46,47 Relapse outcomes in most clinical trials are measured by (a) annualized relapse rate, (b) average number of relapses per patient, (c) proportion of patients who are relapse free, and (d) the cumulative probability of relapse. 48 While annualized relapse rate, or the number of confirmed relapses per patient per year, is commonly used as the primary outcome measure in MS studies, 48 it is difficult to compare annualized relapse rate with the relapse results of older trials of IM IFNβ-1a, 8 SC IFNβ-1b, 3 SC IFNβ-1a, 17 and glatiramer acetate 12 that used relapse counts per year as the primary outcome measure.…”
Section: 42mentioning
confidence: 99%